Development of Game-Based Game-Based Learning on World War I Materials to Increase the Learning Motivation of Grade XI Students of SMA Negeri 6 Semarang - Adisti Ayuningtyas; R. Seoharso (Jurnal Penelitian Pendidikan, 2026)
This research is motivated by the low learning motivation of students in history subjects, particularly in the World War I material which possesses high narrative and chronological complexity. This study aims to develop and test the feasibility of Wordwall-based interactive learning media using a Game-Based Learning approach at SMA Negeri 6 Semarang. The methodology employed is Research and Development (R&D) with the 4D development model (Define, Design, Develop, Disseminate). Data were collected through observations, interviews, and Likert scale questionnaires distributed to 31 eleventh-grade students. Data analysis was conducted using descriptive quantitative methods to measure the media's feasibility level. The results at the Disseminate stage show that the Wordwall media achieved a feasibility rate of 82.39% categorized as Very Feasible. The findings indicate that the use of gamification features and interactivity in Wordwall effectively escalates students' learning motivation and shifts the history learning paradigm towards a more dynamic and students-centered approach.